2007
DOI: 10.1016/j.ceca.2007.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Some assembly required: Constructing the elementary units of store-operated Ca2+ entry

Abstract: SUMMARYThe means by which Ca 2+ store depletion evokes the opening of store-operated Ca 2+ channels (SOCs) in the plasma membrane of excitable and non-excitable cells has been a longstanding mystery. Indirect evidence has supported local interactions between the ER and SOCs as well as long-range interactions mediated through a diffusible activator. The recent molecular identification of the ER Ca 2+ sensor (STIM1) and a subunit of the CRAC channel (Orai1), a prototypic SOC, has now made it possible to visualiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
61
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(63 citation statements)
references
References 76 publications
(143 reference statements)
2
61
0
Order By: Relevance
“…Both co-localization analyses revealed that the degree of Cherry-STIM1 and RyR2 S437 -YFP co-localization in puncta increased significantly following Co-localization of RyR and STIM1 in the puncta following store depletion provides a structural basis for the bidirectional interaction between RyR and CRAC channel machinery. It is established that translocation of STIM1 within the ER membrane to the ER-plasma membrane junctional sites, and formation of puncta following a decline in [Ca 2ϩ ] ER promotes STIM1 coupling with the CRAC channel pore-forming ORAI1 protein and CRAC channel opening (12,48,49,51,52). It was also shown that SERCA co-localize with STIM1 puncta following store depletion (53,54).…”
Section: Ryr Expression and Function Are Up-regulated Upon Primary Humentioning
confidence: 97%
See 1 more Smart Citation
“…Both co-localization analyses revealed that the degree of Cherry-STIM1 and RyR2 S437 -YFP co-localization in puncta increased significantly following Co-localization of RyR and STIM1 in the puncta following store depletion provides a structural basis for the bidirectional interaction between RyR and CRAC channel machinery. It is established that translocation of STIM1 within the ER membrane to the ER-plasma membrane junctional sites, and formation of puncta following a decline in [Ca 2ϩ ] ER promotes STIM1 coupling with the CRAC channel pore-forming ORAI1 protein and CRAC channel opening (12,48,49,51,52). It was also shown that SERCA co-localize with STIM1 puncta following store depletion (53,54).…”
Section: Ryr Expression and Function Are Up-regulated Upon Primary Humentioning
confidence: 97%
“…RyR Co-localize with STIM1 Puncta following Store Depletion-STIM1 is an ER-resident transmembrane protein that senses changes in [Ca 2ϩ ] ER and gates CRAC channels upon change in [Ca 2ϩ ] ER (48). Store depletion triggers translocation of STIM1 proteins to the ER-plasma membrane junctional sites, where they oligomerize and form discrete puncta, which is required for CRAC channel activation (12,35,40,49).…”
Section: Ryr Expression and Function Are Up-regulated Upon Primary Humentioning
confidence: 99%
“…The discoveries of the ER Ca 2þ sensor STIM1 in 2005 and the CRAC channel protein Orai1 a year later marked an unmistakable turning point in the field, as they provided the first and most essential molecular tools with which to dissect the SOCE mechanism. The history of these discoveries and the early revelations they afforded have been reviewed extensively (Cahalan et al 2007;Wu et al 2007;Fahrner et al 2009;Putney 2009;Várnai et al 2009;Hogan et al 2010). In this review, I will summarize our current understanding of how Ca 2þ store depletion leads to Ca 2þ entry at a molecular level, and the role of STIM oligomerization and additional proteins in this process.…”
mentioning
confidence: 99%
“…Most importantly, declining ER [Ca 2+ ] but not increasing cytoplasmic [Ca 2+ ] triggers the activity of the Orai1 channels. This is a crucial distinction, separating it from Ca 2+ -activated transient receptor potential (TRP) and K + channels (2,3).…”
mentioning
confidence: 99%
“…G-protein and tyrosine kinase receptors activate phospholipase C to hydrolyze plasma membrane-specific phosphatidylinositol 4,5-bisphosphate (PIP 2 ) to release soluble inositol triphosphate (IP 3 ) (1). Within seconds, IP 3 gates the ER IP 3 R channel to increase cytoplasmic Ca 2+ . Over the next few minutes, a plasma membrane Ca 2+ entry mechanism [or storeoperated Ca 2+ entry (SOCE)] is activated via a message from the calcium-depleted ER.…”
mentioning
confidence: 99%